Bedtime stories - Madonna; Hooper, Nellee; Babyface; Austin, Dallas; Hall, Dave'Jam'; Maverick Recording Company; Sire Records Company (California : Maverick Recording Company, 1994)
Bedtime Stories is the sixth studio album by American singer-songwriter Madonna, inspired by contemporary R&B and new jack swing, developing a generally more mainstream, radio-friendly sound.
CD 1 : Survival -- Secret -- I'd Rather Be Your Lover -- Don't Stop -- Inside Of Me -- Human Nature -- Forbidden Love -- Love Tried To Welcome Me -- Sanctuary -- Bedtime Story -- Take A Bow.
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Rock music -- 1991-2000.; Popular music -- 1991-2000.